Successful clozapine rechallenge in a patient with suspected drug induced lupus. Issue 4 (3rd April 2019) - Pathak, Suraj; Cherry, Scott; Samad, Samreen; Aftab, Ambreen
Abstract : Clozapine is the most effective treatment for patients with refractory schizophrenia. Clozapine is also associated with serious and potentially lethal side effects including drug induced lupus (DIL). There have been four previous published case reports describing clozapine inducing a lupus-like syndrome including one previous case where a clozapine rechallenge was attempted without success. This case report describes a successful clozapine rechallenge in a patient with suspected DIL.